Development of Sarcoidosis after Successful Treatment of Itsenko–Cushing’s Disease - Sabirdjanovna, Kurbanova Nozima; oʻgʻli, Vaxobov Sherzod Arslon; Baxtiyorovich, Murtozov Bekzod; oʻgʻli, Musurmonov Baxtishod Gʻayrat; oʻgʻli, Pardayev Lazizjon Ulfat; Dilorom, Omonova (Journal of Science in Medicine and Life, 2024)
Itsenko-Cushing's disease is a rare severe neuroendocrine disease caused by chronic overproduction of adrenocorticotropic hormone by a pituitary tumor. High concentrations of cortisol in the blood during endogenous hypercortisolism have an immunosuppressive and anti-inflammatory effect, as does systemic glucocorticosteroid therapy. This may help reduce the activity of the patient’s concomitant autoimmune inflammatory diseases. On the other hand, a decrease in cortisol levels during treatment of Cushing's disease may be associated with reactivation of the immune system, which increases the risk of relapse or onset of various autoimmune diseases. We present our own clinical case demonstrating the difficulties of diagnosing endogenous hypercortisolism in a young patient and the subsequent development of sarcoidosis that arose after successful surgical treatment of Itsenko-Cushing's disease.